Pengaruh Corporate Governance Index terhadap Kinerja Keuangan Perusahaan - Silvianti, Silvianti; Andriana, Isni; Muthia, Fida (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of the corporate governance index on the company’s financial performance. The population in this study were all companies registered in the corporate governance perception index (CGPI) rating program conducted by the independent agency the indonesian institute for corporate governance (IICG) in 2017-2021, totalling 63 companies using a purposive sampling technique. The data collection technique used is documentation. The data analysis technique used is simple linear regression analysis. The data was processed using the statistical product and service solutions (SPSS) program version 26. The result showed that the corporate governance index had a positive and significant effect on the company’s financial performance. Keywords: Corporate Governance Index, Financial Performance